Development of automatic power factor correction device - Mohd Azuari, Mustapha (2009)
Nowadays the life cost more getting higher and higher. People more consider every dollar that they spend in their daily life. The price of gasoline more getting higher every year, this also make the life cost for each family increase. The price of electricity also increases because of the increase gasoline price. The people should spend their money with efficiently to make sure that the money that they spend is totally useful. There have two methods to save the electricity usage; the first one is using the electricity energy with smart, for example when the air-conditioner is not used it should turn off. The second is using the power factor correction technique, but this method just for inductive load such as air-conditioner, washing machine and refrigerator. The inductive load running causes the leading power factor, means the current that used is more and not totally used. To overcome this problem the reactive component is added, the capacitor is added to improve the power factor and also reduce the current that transfer to the inductive load. The microcontroller (PIC) is use as a control element that switching the capacitor to the power line. The sensor is place at the power line to giving the signal to the microcontroller, microcontroller analyze the signal that feed from the sensor. Microcontroller execute the instruction depend to the signal that giving.